Anthropometric characteristics of elite male taekwondo athletes according to weight category and performance level - Can, E.; Kutlay, E.; Quintana, M. S.; Bridge, C. A. (Scientific Journal of Sport and Performance, 2023)
The aim of this study was to: 1) compare the anthropometric characteristics of elite male taekwondo athletes between selected weight categories using the `full` International Society for Advancement of Kinanthropometry (ISAK) profile; and 2) compare the index of sitting height/stature ratio, and lower-limb segment lengths between standards of competitors. Thirty-two elite male taekwondo athletes volunteered to take part and they were categorised according to five competition weight categories (<58, <63, <68, <74, and <87kg). Anthropometric measurements were performed according to the ISAK profile protocol (42 measures), and the data were compared between the weight categories. Athletes were also divided into two groups based upon their previous success and selected variables were compared between the groups. Significant differences were identified in a range of anthropometric variables between athletes` weight categories, including percentage of body fat [%BF], skinfold thickness, measurement girths, lengths and widths, and somatotype components. Such differences were generally more notable between the lighter (<58kg) and heavier (<63, <68, <74, and <87kg) weight categories, with lighter weight categories tending to exhibit lower %BF, skinfold thickness, smaller/shorter specific limb girths, breadths, and lengths, and lower endomorphy when compared with their heavier weight counterparts. International level athletes displayed significantly lower sitting height/ stature ratio, and greater iliospinale and tibiale laterale height than their national level counterparts (p < .05). The findings of this study provide focused reference values to assist preparations for selected weight categories within the sport, and they offer a framework to support talent identification programmes.